2019
DOI: 10.3390/ijms20112745
|View full text |Cite
|
Sign up to set email alerts
|

CAIX Regulates Invadopodia Formation through Both a pH-Dependent Mechanism and Interplay with Actin Regulatory Proteins

Abstract: Tumor metastasis is tightly linked with invasive membrane protrusions, invadopodia, formed by actively invading tumor cells. Hypoxia and pH modulation play a role in the invadopodia formation and in their matrix degradation ability. Tumor-associated carbonic anhydrase IX (CAIX), induced by hypoxia, is essential for pH regulation and migration, predisposing it as an active component of invadopodia. To investigate this assumption, we employed silencing and inhibition of CA9, invadopodia isolation and matrix degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 38 publications
(69 reference statements)
2
43
0
Order By: Relevance
“…The authors showed by PLA that CAIX is closely colocalized with NBCe1 in the lamellipodia of hypoxic A549 adenocarcinomic human alveolar basal epithelial cells [39]. The same group also confirmed the colocalization of CAIX with NBCe1 in the invadopodia of hypoxic HT1080 fibrosarcoma cells [80]. Knockdown of the CAIX protein, as well as pharmacological inhibition of CAIX enzymatic activity or overexpression of a catalytically inactive CAIX mutant, resulted in a decrease in cell migration as well as reduced formation of invadopodia and proteolytic cleavage of the ECM.…”
Section: The Role Of Transport Metabolons In Tumor Ph Regulation and mentioning
confidence: 78%
See 4 more Smart Citations
“…The authors showed by PLA that CAIX is closely colocalized with NBCe1 in the lamellipodia of hypoxic A549 adenocarcinomic human alveolar basal epithelial cells [39]. The same group also confirmed the colocalization of CAIX with NBCe1 in the invadopodia of hypoxic HT1080 fibrosarcoma cells [80]. Knockdown of the CAIX protein, as well as pharmacological inhibition of CAIX enzymatic activity or overexpression of a catalytically inactive CAIX mutant, resulted in a decrease in cell migration as well as reduced formation of invadopodia and proteolytic cleavage of the ECM.…”
Section: The Role Of Transport Metabolons In Tumor Ph Regulation and mentioning
confidence: 78%
“…Knockdown of the CAIX protein, as well as pharmacological inhibition of CAIX enzymatic activity or overexpression of a catalytically inactive CAIX mutant, resulted in a decrease in cell migration as well as reduced formation of invadopodia and proteolytic cleavage of the ECM. The authors further showed that application of monoclonal antibodies against the CAIX catalytic domain or the PG domain inhibits the metastatic properties of TE-1 human squamous cell carcinoma cells in a quail chorioallantoic membrane invasion assay and of HT-2018 cells in a mouse lung colonization assay [80]. Based on these results, the authors concluded that CAIX forms a transport metabolon with NBCe1 in the leading edge of migrating and invading tumor cells.…”
Section: The Role Of Transport Metabolons In Tumor Ph Regulation and mentioning
confidence: 93%
See 3 more Smart Citations